Comparison of Nondestructive Testing Method for Strength Prediction of Asphalt Concrete Material - Al-Mattarneh, Hashem; Dahim, Mohammed (Civil Engineering Journal, 2021)
Concrete is one of the most common construction materials used in rigid pavement, bridges, roads, highways, and buildings. Compressive strength is one of the most important properties of concrete, which determines its quality. This study aims to present the use of a new surface dielectric method to estimate concrete compressive strength. Six concrete mixtures were produced with compressive strengths ranging from 30 to 60 MPa. Compressive strength and strength development were determined during 28 days of curing. All concrete mixes were tested using the ASTM standard. The dielectric properties, ultrasound velocity, and rebound number of all concrete mixes were also measured at each day of curing. The results obtained from the proposed dielectric method in predicting the compressive strength of concrete were compared with the rebound hammer and ultrasonic velocity that are frequently used to evaluate the compressive strength of concrete.Â  The dielectric method shows a higher square correlation coefficient than the other two methods. The results also indicate that combined more than one method of nondestructive techniques will lead to higher prediction and could help to reduce some errors associated with using a certain method alone. The result indicate that the finding of this study could lead to help in reducing the time of evaluating concrete during construction and could also provide tools for practicing engineer to take decision faster with more confidence level on quality of concrete.Â Doi: 10.28991/cej-2021-03091645 Full Text: PDF